Marine Heatwaves Overwhelm the Buffering Benefits of Marine Protected Areas: Two Decades of Collapse in a Mediterranean Gorgonian - Yanis Zentner; Joaquim Garrabou; Pol Capdevila; Daniel Gómez‐Gras; Graciel·la Rovira; Alba Medrano; Frederic Zuberer; Jean‐Baptiste Ledoux; Diego K. Kersting; Mikel Zabala; Cristina Linares (Global Change Biology, 2026)
Marine heatwaves (MHWs) are driving mass mortalities of coastal foundation species globally, threatening their persistence and the ecosystems they support. However, long‐term demographic evidence of these impacts at regional scales is scarce. Accordingly, whether ongoing conservation actions, mainly marine protected areas (MPAs), mitigate the impact of MHWs is still an open question. Here, we address these gaps by analysing over two decades of demographic monitoring data from 49 shallow ( Paramuricea clavata paired with in situ temperature records across the north‐western Mediterranean (38°–43° N, 0°–8° E). Using hierarchical Bayesian models, we estimated regional‐scale trends and assessed the combined influence of MHW exposure and protection status. We found that increasingly frequent extreme thermal events have caused widespread mass mortality, resulting in a 45% median decline in biomass at the regional scale over the past two decades. Within this context of extensive decline, protection temporarily buffered MHW impacts by sustaining higher overall biomass, despite protected populations experiencing greater absolute losses. Taken together, these findings indicate that local protection alone cannot offset climate‐driven mortality and underscore the urgent need to integrate conservation measures with global climate action to preserve shallow marine ecosystems.

Contrasting vulnerability profiles for insular assemblages of birds and mammals facing global change - Clara Marino; Ana Benítez‐López; Nathalie Butt; Gabriel Caetano; Pol Capdevila; Pierre Denelle; Adrienne Etard; José María Fernández Palacios; Iago Ferreiro‐Arias; Camille Leclerc; Jonathan Lenoir; Martin Philippe‐Lesaffre; et al. (Conservation Biology, 2026)
Island biota is currently threatened by global anthropogenic pressures. The limited ability of island species to track suitable conditions and their inherent sensitivity to anthropogenic changes make insular biota highly vulnerable to global threats. Although vulnerability assessments of species to single threats individually have been conducted, the vulnerability of island faunas to multiple global change drivers has not. We evaluated the relative vulnerability of 266 insular bird and mammal species from 45 islands in six well‐studied archipelagos to multiple threats. We first quantified the current exposure of islands to climate change, land‐use change, and biological invasions. We then calculated insular assemblage sensitivity based on species’ ecological characteristics, such as diet and habitat specialization, generation length, and geographical rarity. To assess the adaptive capacity of insular species in response to these threats, we examined biotic and abiotic features, such as species’ dispersal ability, terrain heterogeneity, and proportion of protected area. Exposure and adaptive capacity markers varied greatly among the six archipelagos, but the mean sensitivity of assemblages was similar across islands. Hawai'i, the Azores, and the Mascarenes had high vulnerability scores. Climate change and biological invasions were dominant threats in Hawai'i, and land‐use change was the dominant threat in the Mascarenes, Azores, and Canaries. Assemblages from the Galapagos and Tristan da Cunha had lower vulnerability to current threats. The differences in vulnerability among island assemblages, mostly arising from differences in exposure and adaptive capacity, mean these islands’ conservation needs differ. Our results delineate the mechanisms behind the vulnerability of insular biota under global change, a necessary step to effectively preserve island biodiversity and its associated human benefits.

Global Warming Drives Phenological Shifts and Hinders Reproductive Success in a Temperate Octocoral - Núria Viladrich; Andrea Gori; Pol Capdevila; Maria Montseny; Andreu Santín; Ignasi Montero‐Serra; Marta Pagès‐Escolà; Joaquim Garrabou; Cristina Linares (Global Change Biology, 2026)
Global warming is profoundly reshaping biodiversity. Until now, most research has focused on the impacts of extreme temperature events. However, in many ecosystems, it is becoming increasingly apparent that climate change is accelerating the onset of spring warming conditions. These advanced warming conditions can significantly disrupt critical biological processes such as reproduction, which is key for population persistence. While interest in phenological shifts has increased in recent years, their effects on marine foundation species, such as corals, remain poorly understood. Here, we combined observational and experimental approaches to assess the effects of advanced spring warming conditions driven by climate change on the reproduction of the Mediterranean octocoral Paramuricea clavata , a foundation species. Our findings reveal that a 2°C warming leads to a 2‐week advancement in P. clavata spawning, as evidenced by both field observations, and ex‐situ experiments. These results underscore the role of advanced spring warming as a significant driver of phenological shifts in coastal marine ecosystems. Furthermore, we show that this phenological shift lead to a reduction in the number of spawning events, as well as decreases in larval biomass, survival rates, and settlement success. These findings highlight the urgent necessity to monitor phenological changes in foundational marine species, as such shifts can undermine the long‐term viability of coral populations and contribute to substantial decline in associated biodiversity. Consequently, the increased vulnerability of species caused by phenological responses driven by seasonal changes may lead to more dramatic consequences of ocean warming than previously anticipated.

Novel Regimes of Extreme Climatic Events Trigger Negative Population Rates in a Common Insect - Maria Vives‐Ingla; Pol Capdevila; Christopher F. Clements; Constantí Stefanescu; Jofre Carnicer (Global Change Biology, 2025)
The IPCC predicts that events at the extreme tail of the probability distribution will increase at a higher rate relative to less severe but still abnormal events. Such outlier events are of particular concern due to nonlinear physiological and demographic responses to climatic exposure, meaning that these events are expected to have disproportionate impacts on populations over the next decades (so called low‐likelihood, high‐impact events —LLHI). Because such events are historically rare, forecasting how biodiversity will respond requires mechanistic models that integrate the fundamental processes driving biological responses to our changing climate. Here we built a matrix population model (MPM) from long‐term monitored populations of an insect model species in a Mediterranean area. The model simultaneously integrates the effects of extreme microclimatic heat exposure and drought‐induced host‐plant scarcity on early life stages, a key methodological step forward because these understudied life stages are usually very susceptible to climatic events. This model for the first time allowed us to forecast the demographic impacts that LLHI events will have on a well‐known insect considering their whole life cycle. We found that juveniles were the life stage with the largest relative contribution to population dynamics. In line with field observations, simulated population rates in current climatic regimes were importantly determined by drought impacts, producing a regional mosaic of non‐declining and declining populations. The simulations also indicated that in future, climate scenarios not meeting the Paris Agreement, LLHI heat extremes triggered regionally widespread and severe declines in this currently abundant species. Our results suggest that LLHI events could thus emerge as a critical new —but overlooked— driver of the declines in insect populations, risking the crucial ecosystem functions they perform. We suggest that process‐based and whole‐cycle modelling approaches are a fundamental tool with which to understand the true impacts of climate change.

The importance of locally sourced data in identifying population trends: Insights from Iberian vertebrates - Roberto C. Rodríguez-Caro; Zebensui Morales-Reyes; Alba Aguión; Rebeca Arias-Real; Eneko Arrondo; Eneko Aspillaga; Jordi Boada; Andrea Campos-Candela; Mónica Expósito-Granados; Aitor Forcada; Robin Freeman; Miguel Ángel Gómez-Serrano; et al. (Biological Conservation, 2024)

Recent exposure to environmental stochasticity does not determine the demographic resilience of natural populations - James Cant; Pol Capdevila; Maria Beger; Roberto Salguero‐Gómez (Ecology Letters, 2023)
Escalating climatic and anthropogenic pressures expose ecosystems worldwide to increasingly stochastic environments. Yet, our ability to forecast the responses of natural populations to this increased environmental stochasticity is impeded by a limited understanding of how exposure to stochastic environments shapes demographic resilience. Here, we test the association between local environmental stochasticity and the resilience attributes (e.g. resistance, recovery) of 2242 natural populations across 369 animal and plant species. Contrary to the assumption that past exposure to frequent environmental shifts confers a greater ability to cope with current and future global change, we illustrate how recent environmental stochasticity regimes from the past 50 years do not predict the inherent resistance or recovery potential of natural populations. Instead, demographic resilience is strongly predicted by the phylogenetic relatedness among species, with survival and developmental investments shaping their responses to environmental stochasticity. Accordingly, our findings suggest that demographic resilience is a consequence of evolutionary processes and/or deep‐time environmental regimes, rather than recent‐past experiences.

Marine protected areas in a changing ocean: Adaptive management can mitigate the synergistic effects of local and climate change impacts - Yanis Zentner; Graciel·la Rovira; Núria Margarit; Júlia Ortega; David Casals; Alba Medrano; Marta Pagès-Escolà; Eneko Aspillaga; Pol Capdevila; Laura Figuerola-Ferrando; Joan Lluís Riera; Bernat Hereu; et al. (Biological Conservation, 2023)

Marine heatwaves drive recurrent mass mortalities in the Mediterranean Sea - Joaquim Garrabou; Daniel Gómez‐Gras; Alba Medrano; Carlo Cerrano; Massimo Ponti; Robert Schlegel; Nathaniel Bensoussan; Eva Turicchia; Maria Sini; Vasilis Gerovasileiou; Nuria Teixido; Alice Mirasole; et al. (Global Change Biology, 2022)
Climate change is causing an increase in the frequency and intensity of marine heatwaves (MHWs) and mass mortality events (MMEs) of marine organisms are one of their main ecological impacts. Here, we show that during the 2015–2019 period, the Mediterranean Sea has experienced exceptional thermal conditions resulting in the onset of five consecutive years of widespread MMEs across the basin. These MMEs affected thousands of kilometers of coastline from the surface to 45 m, across a range of marine habitats and taxa (50 taxa across 8 phyla). Significant relationships were found between the incidence of MMEs and the heat exposure associated with MHWs observed both at the surface and across depths. Our findings reveal that the Mediterranean Sea is experiencing an acceleration of the ecological impacts of MHWs which poses an unprecedented threat to its ecosystems' health and functioning. Overall, we show that increasing the resolution of empirical observation is critical to enhancing our ability to more effectively understand and manage the consequences of climate change.

Life history mediates the trade‐offs among different components of demographic resilience - Pol Capdevila; Iain Stott; James Cant; Maria Beger; Gwilym Rowlands; Molly Grace; Roberto Salguero‐Gómez (Ecology Letters, 2022)
Accelerating rates of biodiversity loss underscore the need to understand how species achieve resilience—the ability to resist and recover from a/biotic disturbances. Yet, the factors determining the resilience of species remain poorly understood, due to disagreements on its definition and the lack of large‐scale analyses. Here, we investigate how the life history of 910 natural populations of animals and plants predicts their intrinsic ability to be resilient. We show that demographic resilience can be achieved through different combinations of compensation, resistance and recovery after a disturbance. We demonstrate that these resilience components are highly correlated with life history traits related to the species’ pace of life and reproductive strategy. Species with longer generation times require longer recovery times post‐disturbance, whilst those with greater reproductive capacity have greater resistance and compensation. Our findings highlight the key role of life history traits to understand species resilience, improving our ability to predict how natural populations cope with disturbance regimes.

Global patterns of resilience decline in vertebrate populations - Pol Capdevila; Nicola Noviello; Louise McRae; Robin Freeman; Christopher F. Clements (Ecology Letters, 2022)
Maintaining the resilience of natural populations, their ability to resist and recover from disturbance, is crucial to prevent biodiversity loss. However, the lack of appropriate data and quantitative tools has hampered our understanding of the factors determining resilience on a global scale. Here, we quantified the temporal trends of two key components of resilience—resistance and recovery—in >2000 population time‐series of >1000 vertebrate species globally. We show that the number of threats to which a population is exposed is the main driver of resilience decline in vertebrate populations. Such declines are driven by a non‐uniform loss of different components of resilience (i.e. resistance and recovery). Increased anthropogenic threats accelerating resilience loss through a decline in the recovery ability—but not resistance—of vertebrate populations. These findings suggest we may be underestimating the impacts of global change, highlighting the need to account for the multiple components of resilience in global biodiversity assessments.

Where Is More Important Than How in Coastal and Marine Ecosystems Restoration - Simonetta Fraschetti; Chris McOwen; Loredana Papa; Nadia Papadopoulou; Meri Bilan; Christoffer Boström; Pol Capdevila; Marina Carreiro-Silva; Laura Carugati; Emma Cebrian; Marta Coll; Thanos Dailianis; et al. (Frontiers in Marine Science, 2021)
Restoration is considered an effective strategy to accelerate the recovery of biological communities at local scale. However, the effects of restoration actions in the marine ecosystems are still unpredictable. We performed a global analysis of published literature to identify the factors increasing the probability of restoration success in coastal and marine systems. Our results confirm that the majority of active restoration initiatives are still concentrated in the northern hemisphere and that most of information gathered from restoration efforts derives from a relatively small subset of species. The analysis also indicates that many studies are still experimental in nature, covering small spatial and temporal scales. Despite the limits of assessing restoration effectiveness in absence of a standardized definition of success, the context (degree of human impact, ecosystem type, habitat) of where the restoration activity is undertaken is of greater relevance to a successful outcome than how (method) the restoration is carried out. Contrary to expectations, we found that restoration is not necessarily more successful closer to protected areas (PA) and in areas of moderate human impact. This result can be motivated by the limits in assessing the success of interventions and by the tendency of selecting areas in more obvious need of restoration, where the potential of actively restoring a degraded site is more evident. Restoration sites prioritization considering human uses and conservation status present in the region is of vital importance to obtain the intended outcomes and galvanize further actions.